2018
DOI: 10.1097/igc.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Examining Survival Outcomes of 852 Women With Advanced Ovarian Cancer: A Multi-institutional Cohort Study

Abstract: In this multicenter study, 53% of women with advanced HGSC seen by a gynecologic oncologist were selected for PCS. Survival was longer in patients who underwent PCS than patients who underwent NACT. Within each group, survival was highest in those who had complete cytoreduction to 0-mm residual disease. We believe all patients with advanced HGSC should be assessed by a gynecologic oncologist for the feasibility of surgical resection. Primary cytoreductive surgery should be the favorable treatment modality with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…The risk of death and disease recurrence were reduced by 43% and 48%, respectively, for patients with no visible disease compared to those with >1 cm residual disease. These results corroborate the findings of a recent study from Canada, in which CGR is cited as an independent prognostic factor for improved OS [26]. An important study by Chang et al further supports the significance of CGR on survival [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The risk of death and disease recurrence were reduced by 43% and 48%, respectively, for patients with no visible disease compared to those with >1 cm residual disease. These results corroborate the findings of a recent study from Canada, in which CGR is cited as an independent prognostic factor for improved OS [26]. An important study by Chang et al further supports the significance of CGR on survival [10].…”
Section: Discussionsupporting
confidence: 89%
“…Thirty-day mortality decreased over time from 0.6% to 0%, and 90-day mortality also decreased from 2.9% to 0%. Several studies have shown similar results, citing major complication rates of 18.8% to 20.8% and 30-day mortality rates of 0.2% to1.3% [15, 2526]. Performing more extensive surgery to achieve better surgical outcomes appears to confer improved survival without compromising patient safety.…”
Section: Discussionmentioning
confidence: 86%
“…The tumor burden estimated according to the PCI could be a useful tool for selecting the ideal therapeutic strategy and quantifying responses to NACT beyond RECIST criteria. In most studies, UDS and NACT‐IDS are compared in advanced tubo‐ovarian cancer and the only criterion referring to tumor load is the FIGO disease stage, generally analyzing data for patients with stage IIIC or IV tumors and including in each group patients in whom peritoneal spread differs widely in extent. Hence an unreliable definition of tumor burden favors a treatment assignment bias that tends to indicate as candidates for NACT‐IDS all the patients whose diagnostic imaging discloses extensive peritoneal spread indicating a possibly worse outcome regardless of other criteria .…”
Section: Discussionmentioning
confidence: 99%
“…To address these matters and determine the ideal treatment strategy, the ongoing Trust trial, enrolling centers guaranteeing high surgical quality and having as its primary endpoint overall survival (OS), randomized 1:1 UDS versus NACT‐IDS, patients with FIGO‐stage IIIB‐IVB tubo‐ovarian and peritoneal carcinoma. Even though surgical quality needs to be more highly standardized, studies comparing UDS versus NACT tend to overlook the need to analyze data for a specific tumor histotype or, quantify precisely the peritoneal tumor burden and evaluate in detail responses to NACT . Equally important, detailed information on the clinical history of the disease, the timing, site, treatment of recurrence, and its results could help in understanding treatment outcome in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies regarding stage IV ovarian cancer patients have reported that the survival outcomes in patients who underwent PDS were lower compared to patients who underwent NACT [14, 15]. In addition, several meta-analyses have suggested that NACT is associated with worst outcomes when compared to standard PDS followed by adjuvant chemotherapy [1619].…”
Section: Introductionmentioning
confidence: 99%